2017
DOI: 10.1187/cbe.16-04-0160
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Alignment with Vision and Change Improves Student Scientific Literacy

Abstract: Students who experienced a reformed introductory curriculum designed to align with the Vision and Change report recommendations demonstrated higher gains in scientific literacy when compared with students who had experienced the previous curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…3). Although peer review was not directly assessed in this project, studies have shown that including a peer review component has increased student learning as well as quality of writing and scientific content (23, 24). …”
Section: Discussionmentioning
confidence: 99%
“…3). Although peer review was not directly assessed in this project, studies have shown that including a peer review component has increased student learning as well as quality of writing and scientific content (23, 24). …”
Section: Discussionmentioning
confidence: 99%
“…This same approach can be adopted for curriculum reform, identifying clear outcomes that students should be able to achieve by the time they graduate, aligning the curriculum to these outcomes, and developing assessments that can both measure and make inferences about student learning across a major (4,16). This approach to curriculum design can serve to help departments better understand how their curriculum is impacting students, which, in turn, can help improve student learning and critical thinking processes (2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, instructors were presumably not motivated by data showing increased student conceptual learning. We did have data showing increased student gains in scientific literacy ( Auerbach and Schussler, 2017 ), but these data were not completed until after year 3. We also do not believe that change was driven by discussions of enjoyment of teaching within the community or changes in student relationships.…”
Section: Discussionmentioning
confidence: 99%